1990
DOI: 10.1016/0012-821x(90)90031-r
|View full text |Cite
|
Sign up to set email alerts
|

Collection of microparticles at high balloon altitudes in the stratosphere

Abstract: We report the collection of stratospheric particles at 34-36 km using balloon-borne collectors. The concentration of particles on the collection surfaces and element concentrations were measured on the majority of the particles using scanning electron microscope (SEM) and proton-induced X-ray emission (PIXE) analysis respectively. Particle morphologies, elemental composition, and electron diffraction data were obtained on a small number of the collected particles using transmission electron microscope (TEM) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…TEM grids were previously used in aerosol collection experiments on stratospheric balloons (e.g. Bigg et al, 1971;Testa et al, 1990;Corte et al, 2012) and sounding rockets (Gumbel, 2007). The sticking probability for nanometre particles accelerated to 1 km s −1 on TEM grids was tested by Reissaus et al (2006).…”
Section: Assemblymentioning
confidence: 99%
“…TEM grids were previously used in aerosol collection experiments on stratospheric balloons (e.g. Bigg et al, 1971;Testa et al, 1990;Corte et al, 2012) and sounding rockets (Gumbel, 2007). The sticking probability for nanometre particles accelerated to 1 km s −1 on TEM grids was tested by Reissaus et al (2006).…”
Section: Assemblymentioning
confidence: 99%
“…Carbonaceous particles (diameter ∼ 0.1 µm) which might be soot although they were not unequivocally identified as such, due to the lack of high-resolution images, were found by Chuan and Woods (1984). Testa et al (1990) found seven poorly graphitized carbon particles in their samples and regarded them as artifacts of carbon films from the TEM grids. As they did not provide images of these particles, they cannot be compared to our findings.…”
Section: Occurrence Of Refractory Carbonaceous Particles In the Stratmentioning
confidence: 99%
“…There are, however, several previous publications which describe the presence of a variety of other refractory particle groups in addition to carbonaceous particles. These additional particle groups include metallic particles (Chuan and Woods, 1984;Sheridan et al, 1994;Chen et al, 1998;Baumgardner et al, 2004;Ebert et al, 2016), meteoritic particles (Murphy et al, 1998(Murphy et al, , 2007Renard et al, 2008, silicates (Testa et al, 1990;Ebert et al, 2016), crustal-type particles (Sheridan et al, 1994;Chen et al, 1998), and Ca-bearing particles (Della Corte et al, 2013;Ebert et al, 2016).…”
Section: Occurrence Of Refractory Carbonaceous Particles In the Stratmentioning
confidence: 99%
“…Probably, the composition and concentration of stratospheric solid particles vary greatly with time, location, and/or altitude. It should be noted that Testa et al (1990) also reported the deficiency of Al-rich grains for the sample collected at 34-36 km altitude in 1984. 4.3 Cr + Fe + Ni particles transported from the surf ace We have found 14 particles composed of Cr, Fe and Ni in the present sample.…”
Section: Deficiency Of Al-rich Particlesmentioning
confidence: 99%
“…Collection of solid (i.e., water insoluble) particles m the stratosphere has been carried out by many researchers (Mossop, 1964;Brownlee et al, 1976;Gooding et al, 1983;Zolensky and Mackinnon, 1985;Zolensky et al, 1989;Testa et al, 1990). These collections have revealed the existence of a remarkable variety of material: (1) volcanic ash, (2) soils and products of rock weathering, (3) rocket exhaust and rocket/satellite debris, and (4) interplanetary dust falling to Earth from space and ablation debris of meteorites (cf.…”
Section: Introductionmentioning
confidence: 99%